2010
DOI: 10.1099/mic.0.038604-0
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of hpdR and its effect on CDA biosynthesis in Streptomyces coelicolor

Abstract: HpdR, an IclR-family regulator in Streptomyces coelicolor, is a substrate-dependent repressor for the tyrosine catabolic gene hppD. In this study, S1 nuclease protection assays revealed that hpdR is subject to a negative autoregulation. Purified HpdR showed specific DNA-binding activity for the promoter region of hpdR, indicating that the autoregulation of hpdR is performed directly. The disruption of hpdR led to reduced production of CDA by S. coelicolor J1501, suggesting a positive effect of hpdR on CDA bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Repression is relieved by 4HPP (111). Remarkably, HpdR also binds to the promoter of the CDA biosynthetic gene hmaS, which encodes an enzyme converting 4HPP to 4-hydroxymandelate (112). Since hmaS transcription is reduced in an hpdR mutant, HpdR functions to activate hmaS.…”
Section: Regulation At a Meeting Point Of Primary And Secondary Metabmentioning
confidence: 99%
See 1 more Smart Citation
“…Repression is relieved by 4HPP (111). Remarkably, HpdR also binds to the promoter of the CDA biosynthetic gene hmaS, which encodes an enzyme converting 4HPP to 4-hydroxymandelate (112). Since hmaS transcription is reduced in an hpdR mutant, HpdR functions to activate hmaS.…”
Section: Regulation At a Meeting Point Of Primary And Secondary Metabmentioning
confidence: 99%
“…Thus, 4HPP acts both as a metabolic intermediate and as a regulatory ligand in the partitioning of tyrosine catabolism between primary and secondary metabolism ( Fig. 7) (112).…”
Section: Regulation At a Meeting Point Of Primary And Secondary Metabmentioning
confidence: 99%
“…Additional qRT-PCR results revealed that transcription of clmR1 also increases in the clmR1 mutant, suggesting that clmR1 expression is downregulated by its own product. Several examples of negative autoregulation have been described to date, such as the case of heat-shock protein regulator HspR, which negatively regulates its own expression along with that of some other genes coding for different chaperone systems (Salerno et al , 2007), or the IclR-family regulator HpdR, which is involved in calcium-dependent antibiotic production by Streptomyces coelicolor (Yang et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The calcium-dependent antibiotic (CDA) assay essentially followed that described by Yang et al (24). Inocula of 10 9 spores of M145, JSE2301, JSE2301/pJSE2255, and JSE2301/pIJ8600 were plated on Oxoid nutrient agar (10 ml) and incubated at 30°C for 3 days.…”
Section: Methodsmentioning
confidence: 99%